Cursing Beyond the Grave: Imprecations and Jewish Funerary Culture in Antiquity - Saʿar, Orṭal-Paz (Entangled Religions, 2022)
This article discusses curses found in ancient and late antique Jewish funerary inscriptions. It begins with a typology of imprecatory texts based on a survey of funerary epigraphy, both Jewish and non-Jewish. It proceeds with an analysis of explicit curse formulae found in a Jewish funerary context: on ossuaries, on the walls of burial caves, or on architectural elements of graves. The article discusses several aspects of these curses, placing them in a physical, religious, and psychological context.